Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1002/ajmg.1320360205
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroiditis associated with mild “subclinical” hypothyroidism in adults with down syndrome: A comparison of patients with and without manifestations of Alzheimer disease

Abstract: Serum tests of thyroid function were compared in Down syndrome (DS) patients with and without manifestations of Alzheimer disease (AD). Relative to control individuals, DS patients had, overall, lower mean total T4 (P = 0.070) and T3f (P = 0.015), higher T3U (P = 0.013) and TSH (P = 0.020), no difference in free T4, and higher thyroid antithyroglobulin (ATA) (P = 0.033) and antimicrosomal autoantibody (AMA) titres (P = 0.0097). Similar trends were apparent in DS males and females, and in DS patients off all dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…Furthermore, it has been suggested a link between subclinical hypothyroidism and autoimmune-based risk of dementia in people genetically predisposed, for example those with Down's syndrome [40]. Therefore, it cannot ruled out the possibility that thyroid autoimmune phenomena, regardless of their impact on thyroid function, may play a direct role in the impairment of cognitive state observed in elderly subjects with subclinical hypothyroidism [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested a link between subclinical hypothyroidism and autoimmune-based risk of dementia in people genetically predisposed, for example those with Down's syndrome [40]. Therefore, it cannot ruled out the possibility that thyroid autoimmune phenomena, regardless of their impact on thyroid function, may play a direct role in the impairment of cognitive state observed in elderly subjects with subclinical hypothyroidism [36].…”
Section: Discussionmentioning
confidence: 99%
“…There is a clinical correlation between autoimmune Hashimoto's thyroiditis and Down's syndrome, with the strongest correlation in patients with Down's syndrome that manifest with AD pathology (10).…”
Section: Discussionmentioning
confidence: 99%
“…CNS-specific hypothyroidism, as defined by reduced triiodothyronine (T 3 ) and elevated reverse T 3 (rT 3 ) in cerebrospinal fluid (CSF), was recently reported in euthyroid patients with AD (5). The incidence of autoimmune thyroiditis is significantly increased in patients with Down's syndrome and is correlated with manifestations of AD pathology in these patients (10). A direct relationship between thyroid hormone and AD neuropathology has been suggested, as thyroid hormone is a negative regulator of APP gene expression in vitro (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…There is no definite evidence showing that thyroid disorders predisposes to AD in the Down syndrome population. However, Percy et al (1990) suggested that "subclinical" hypothyroidism may contribute to cognitive deficits in ageing Down syndrome patients and Bhaumik et al (1991) have shown that elevated levels of TSH in a group of patients with Down syndrome inversely correlated with scores of global adaptive abilities. Although further research is required, it is unlikely that thyroid hormone estimation is of any clinical value as a peripheral marker of Alzheimer's disease .…”
Section: Iii) Dementia (Alzheimer's Disease)mentioning
confidence: 99%